1982
DOI: 10.1002/mus.880050606
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral branched‐chain amino acid treatment and avian dystrophy

Abstract: Genetically homozygous line 413 dystrophic chickens were given twice-daily intraperitoneal injections of solutions containing branched-chain amino acids (BCCA-leucine, valine, isoleucine) either alone or in combination; and their alpha-ketoacid analogs (alpha-ketoisocaproic and alpha-ketoisovaleric acids). Another trial consisted of an amino acid mixture containing BCAA. Amino acid supplementation in each case significantly prolonged righting ability measured regularly by a standardized flip-test procedure. En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1983
1983
1988
1988

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 45 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Another disease associated with considerable wasting of muscle protein is muscular dystrophy. Hudecki et al (1982) found that twicedaily injections of BCAA increased righting ability measured by standardized flip-test procedure of chickens with muscular dystrophy.…”
Section: In Vivo Nitrogen Balancementioning
confidence: 95%
See 1 more Smart Citation
“…Another disease associated with considerable wasting of muscle protein is muscular dystrophy. Hudecki et al (1982) found that twicedaily injections of BCAA increased righting ability measured by standardized flip-test procedure of chickens with muscular dystrophy.…”
Section: In Vivo Nitrogen Balancementioning
confidence: 95%
“…When KIC was administered twice-daily to chickens with muscular dystrophy, righting ability was improved, pectoralis major muscle mass and protein content was increased and the number of degenerating muscle fibers were decreased (Hudecki et al, 1982).…”
Section: In Vivo Nitrogen Balancementioning
confidence: 99%